Use of chloroplast DNA polymorphisms for the phylogenetic study of seven Phaseolus taxa including P. vulgaris and P. coccineus - Schmit, Véronique; Jardin, Paul du; Baudoin, Jean-Pierre; Debouck, Daniel G. (Springer, 1993)
The genetic variable of seven Phaseolus taxa has been evaluated on the basis of molecular data and the results have used to clarify the phyletic relationships between several taxa of the P. coccineus L. complex. Chloroplast DNA (cpDNA) from 33 populations was digested with six restriction endonucleases, revealing some polymorphisms that made it possible to divide most of the taxa into two main groups: the subspecies of P. coccineus on the one hand and P. vulgaris L., P. polyanthus Greenman and P. costaricensis (Freytag and Debouck) on the other hand. P. polyanthus is closer to P. vulgaris than the other taxa of the second group and should be considered as a separate species. The position of the wild species P. costaricensis is intermediate between P. coccineus and P. polyanthus. P. glabellus shows sufficient polymorphisms at the cpDNA level to be recognized as a separate species, as previously suggested from total seed-protein electrophoretic studies. These results favour the hypothesis of a common phylogeny for P. vulgaris, P. polyanthus, P. costaricensis, and P. coccineus from a single wild ancestor. Although cpDNA is generally known to be uniform at the intraspecific level, some additional polymorphisms were also detected within P. vulgaris, P. polyanthus and P. coccineus. Further studies are required to understand the significance of the latter.